Characterisation and analysis of harmonic emissions in nonlinear bulk acoustic wave resonators. Issue 21 (1st October 2013) - Shin, J.‐S.; Song, I.; Ai, Y.; Hwang, S.; Rieh, J.‐S.
Abstract : Harmonic emissions of nonlinear bulk acoustic wave (BAW) resonators with their different configurations are demonstrated and analysed. With the anti‐polarisation configuration of the piezoelectric resonators, the second harmonic emissions are dramatically reduced. However, the anti‐series configuration of dual BAW resonators exhibits a sharp increase in second harmonic emissions near the anti‐resonance frequency. By investigating the phase difference of the generated harmonic waves, the reason for that sharp increase has been successfully analysed.